A comparison of subjective and objective procedures in the admissions process of veterinary students - Kogan, Lori Renei, author; Hamilton, Scott B., advisor; Viney, Wayne, advisor; Boyer, William N., committee member; McConnell, Sherry, committee member (Colorado State University. Libraries, 2002)
In the arduous path leading to the position of a veterinarian is an opportunity limited to a select number of individuals. While admission committees have traditionally focused on objectively defined, cognitive abilities, numerous noncognitive qualities (i.e., problem-solving, critical thinking, communication skills, personal integrity, and empathy) that contain a subjective component have also been identified as important characteristics of veterinary students as well as practicing professionals. A subjective admissions policy may offer a preferable alternative to traditional objective admissions procedures by permitting the evaluation of noncognitive criteria without compromising cognitive standards. The present study was designed to assess Colorado State University's College of Veterinary Medicine and Biomedical Sciences subjective admissions procedure and compare it to their previously employed objective admissions procedure. The first component of the study compared student applications (cognitive and noncognitive components) from the graduating classes 1998, 1999, and 2000 (i.e., objective admissions policy) with student applications from graduating classes of the 2001 and 2002 (i.e., subjective admissions policy). This was accomplished through a comparison of undergraduate academic performance, work history, college and community activities, written essays, and recommendation letters. The second element of the study compared students admitted through the subjective policy with those admitted through the objective policy in terms of veterinary school performance. This was done through a comparison of the graduation rates, cumulative grade point average, and clinical rotation grades of students admitted in the "objective years" with those students in the "subjective years." Two raters independently coded all application categories and rotation grade sheets from which dependent measures were drawn. Results showed that the objective and subjective admissions procedures were equivalent in terms of students' previous academic performance, work experience, college and community activities, as well as success in veterinary school. Due to benefits of a subjective admissions procedure in terms of faculty and applicant preference, and the equivalence of the procedures in terms of student qualifications and performance, it was concluded that the subjective system has benefits outweighing the objective procedure. Limitations of the current study include a five year sample from one veterinary school and the inability to control for historical changes.
Keywords: social psychology; higher education; educational psychology